Nursing Management for Covid 19 Pandemics (Indian Journal of Forensic Medicine & Toxicology, 2021)
Nurses represent the backbone of any health care system. Today in the fight against Covid-19, several nursesfind themselves on the frontline. This report is a clear reminder of their important position and a wake-upcall to ensure that they receive the help they need to keep the planet safe. 1 Nurses play a very importantfunction, locally as well as internationally. They are on the front lines, day in and day out, taking care ofthese patients. “They are able to see what is working, as well as things that can be done differently to providemore effective and efficient care, and offer suggestions for improvement.” 2020 is recognized by the WorldHealth Organization as the Year of the Nurse and Midwife – On the function of nurses in the preparationand reaction to disasters. (World Health Organization) Globally, the way the world views nurses and healthcare professionals already changes. Because not everyone knows what is happening in a health care facility,the COVID-19 pandemic is high The COVID-19 pandemic has brought nurses to the forefront of people’sminds and there is a daily capture of the media attention and public gratitude to health care professionals.2This short communication concludes with the key role of nurses for effective management during covid-19pandemics.
Keywords: COVID-19, pandemic, messenger, educator, advisor, protector,manager,care provider